CCP encyclopedia of Philippine art (Cultural Center of the Philippines and Distributed Processing Systems, 1998)
National Artist Awards and those who passed away since 1994. All other entries follow the cut-off date of 1992 set by the first edition. It also contains video clips of Filipino films, theater and dance, and audio samples of Philippine music and musical instruments